Development of MSMEs in Serang Regency with the Assistance of Creating Business Identification Numbers Through a Risk-Based Online Single Submission System - Haquei, Fitria; Sandra, Mela (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The development of MSMEs in Serang Regency is increasing every year, but there are many obstacles faced by MSMEs (Micro, Small, and Medium Enterprises) in Serang Regency, especially not understanding licensing issues (NIB); many business actors ignore business permits so that their presence is considered inactive or not There is. The purpose of this study is to provide MSME assistance to assist business actors in accelerating the process of issuing business licenses (NIB) by service standards and provide time certainty in the licensing process through the RBA-based Online Single Submission (OSS) System (Risk) until the licensing stage is given to the perpetrators. Business in the form of a certificate or official proof of business legality so that MSMEs can develop their business and be competitive. The results of this study are that many MSMEs in Serang Regency still need to understand the importance of issuing a risk-based Business Identification Number (NIB) as official business legality. The MSME mentoring activity is expected to help MSME access the OSS system up to the stage of clicking the print icon if the applicant is willing to save the complex file of the NIB certificate. The method used in this study consisted of 3 stages: field surveys and interviews, counseling related to NIB, and implementation of assistance in making risk-based NIB through the OSS system, which was then documented. The number of MSMEs that have participated in counseling is 100 MSMEs. Still, from the results of counseling, those interested in participating in the assistance for making NIB are as many as 75 MSMEs, and the remaining 25 MSMEs are constrained by time because they cannot leave their business activities. Help in making NIB was carried out with 75 MSMEs, but 50 MSMEs succeeded in making NIB, so they obtained NIB legality certificates, and 25 other MSMEs experienced data completeness problems.